Giants at the Gate: On the Cross-Section of Private Equity Investment Returns - Florencio Lopez-de-Silanes; Ludovic Phalippou; Oliver Gottschalg (Tinbergen Institute, 2011)
We examine the determinants of private equity returns using a newly constructed database of 7,500investments worldwide over forty years. The median investment IRR (PME) is 21% (1.3), gross offees. One in ten investments goes bankrupt, whereas one in four has an IRR above 50%. Only one ineight investments is held for less than 2 years, but such investments have the highest returns. Thescale of private equity firms is a significant driver of returns: investments held at times of a highnumber of simultaneous investments underperform substantially. The median IRR is 36% in thelowest scale decile and 16% in the highest. Results survive robustness tests. Diseconomies of scaleare linked to firm structure: independent firms, less hierarchical firms, and those with managers ofsimilar professional backgrounds exhibit smaller diseconomies of scale.
Keywords: G24; 330; private equity; diseconomies of scale; Private Equity; Investition; Skalenertrag; Multinationales Unternehmen; USA; Europa